Avaliação da toxicidade de dispersões sólidas contendo berberina utilizando Drosophila melanogaster - Marcelo, Janmille Monteiro (2021)
Berberine is a bioactive compound, specifically an isoquinoline alkaloid of the protoberberine type present in plants belonging to the Berberidaceae family. It presents known antioxidant, anti-inflammatory and neuroprotective activity. However, it has low oral bioavailability, low water solubility and chemical instability, which limits its application in foodstuff. Nanotechnology represents a great advance for the food industry in recent decades and has been applied by industries aiming at the development of new products, in addition to overcome limitations of bioactive compounds. However, it is important to determine the toxicity of these nanoencapsulated compounds in order to ensure food safety. Several species are being used as model organisms for in vivo toxicology studies, including Drosophila melanogaster (Dm), also known as the fruit fly. The aim of this study was to verify the toxicity of berberine-containing nanoparticles using Drosophila melanogaster as an alternative biological model. The production of particles was carried out using the solid dispersion technique. The survival rate of the flies was evaluated daily during the 5 days of treatment, at which time the tissue of the flies was homogenized and tested in an ex vivo model for the activities of the cholinergic enzymes acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), as well as the antioxidant enzymes (catalase (CAT), superoxide dismutase (SOD) and glutathione (GSH)). The characterization techniques showed that the production of solid dispersion containing berberine was efficient. The solid dispersion containing berberine did not change the mortality rate significantly in the doses (3, 10 and 30 μM) evaluated in relation to the control. Berberine played a neuroprotective and antioxidant role, keeping cholinergic enzymes and antioxidant enzymes in cellular balance.